2000
DOI: 10.1021/cm000017g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Na1+xFe4P12 Whiskers by Hydrothermal Reduction Alloying Synthesis Method

Abstract: Skutterudite Na1+ x Fe4P12 whiskers were prepared by a new hydrothermal reduction alloying method. The diameter of the whisker is about 0.5−4 μm and its L/D ratio is about 10−20. Heating temperature and time can control the diameter and length of the skutterudite whisker. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscope (TEM), electronic diffraction (ED), and X-ray fluorescence analysis have been employed to characterize the products. XRD and ED revealed that the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…82). One exception is the sodium‐containing filled skutterudite type polyphosphide Na 1+ x Fe 4 P 12 with excess sodium ( x ≈1), which has been prepared hydrothermally 83. Another, very interesting exception is the series of metastable phosphides Ln Fe 4 P 12 , where the Ln components are late‐rare‐earth elements.…”
Section: The Tin Fluxmentioning
confidence: 99%
“…82). One exception is the sodium‐containing filled skutterudite type polyphosphide Na 1+ x Fe 4 P 12 with excess sodium ( x ≈1), which has been prepared hydrothermally 83. Another, very interesting exception is the series of metastable phosphides Ln Fe 4 P 12 , where the Ln components are late‐rare‐earth elements.…”
Section: The Tin Fluxmentioning
confidence: 99%
“…81 Die Herstellung solcher Polyphosphide ohne Zinnflux erfolgte hauptsächlich bei hohen Drücken (Literaturangaben findet man in einem Übersichtsartikel82). Eine Ausnahme bildet das Polyphosphid Na 1+ x Fe 4 P 12 mit überschüssigem Natrium ( x ≈1), das hydrothermal hergestellt wurde 83. Eine weitere bemerkenswerte Ausnahme bildet die Serie der metastabilen Phosphide Ln Fe 4 P 12 ( Ln steht für die schweren Lanthanoide).…”
Section: Zinn Als Flussmittelunclassified
“…Up to now, there has been little work on the synthesis of thermoelectric material nanostructures by wet-chemical methods. Previously our group synthesized skutterudite nanowires for thermoelectric applications [17,18]. Sander et al [19] have reported an electro-deposition method for the synthesis of Bi 2 Te 3 nanowires by using porous anodic alumina templates.…”
Section: Introductionmentioning
confidence: 99%